Algal-derived dissolved organic matter accelerates mercury methylation under cyanobacterial blooms in the sediment of eutrophic lakes - Wang, Yan; Zhang, Lan; Chen, Xiang; Li, Cai; Ding, Shiming; Yan, Jiabao; Xiao, Jing; Wang, Bin; Xu, Lv; Hang, Xiaoshuai (Environmental research, 2024)
Mercury (Hg), especially in the form of methylmercury (MeHg), poses a significant threat to both organisms and the environment due to its extreme toxicity. While methylation process of Hg in sediments has been extensively studied, recognition of its associated risks and mechanisms during cyanobacterial blooms remains limited. This study investigated the distribution characteristics of Hg and MeHg in sediments of Taihu Lake, China. The concentration of Hg and MeHg varied within the range of 96.0–212.0 ng g−1 and 0.1–0.5 ng g−1, respectively. Higher ecological risks of Hg were found in algal-dominated regions compared to macrophyte areas. The significant correlations observed between Hg, MeHg, and algal-derived dissolved organic matter (ADOM) components C1 and C2 in algal-dominated regions indicate a close association between ADOM components and the Hg methylation process. These components are involved in the absorption or complexation of Hg, participate in redox reactions, and modulate microbial activity. The dsrB gene in sulfate-reducing bacteria (SRB) was found to accelerate the metabolic pathways of Hg methylation. These findings indicate that ADOM could enhance the methylation process of Hg during cyanobacterial blooms, which warrants attention. [Display omitted] •Algal-derived DOM increased the mercury methylation in the presence of cyanobacterial blooms.•DsrB gene plays a key role in the metabolic pathways related to mercury reduction and methylation under anoxic conditions.•Vertical distribution of mercury/methylmercury in pore water were obtained simultaneously using high resolution DGT methods.